The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3892/wasj.2021.114
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the photodynamic therapeutic effects of 5‑aminolevulinic acid on human colon cancer cells using light‑emitting diodes

Abstract: The minimal invasiveness and high selectivity of 5-aminolevulinic acid (5-ALA)-based photodynamic therapy (PDT; 5-ALA-PDT) renders it a viable therapeutic option for the treatment of various types of cancer. Compared with conventional lasers, light-emitting diodes (LEDs) are an inexpensive and convenient low-energy light source option. Nevertheless, the scope of LEDs in the 5-ALA-PDT of colorectal cancer (CRC) has yet to be fully determined. Thus, the aim of the present study was to assess the efficacy of LEDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Et when comparing the two types of treatments, PDT and dark. This low reduction in cell viability is not related to exposure to LED, considering that cell viability is higher when cells were exposed to PDT (Figure 5A), which was also observed in studies by Shah et al [31], in which they evaluated the photodynamic activity of four types of LEDs when cancer cells were exposed to them. Furthermore, it was observed that LEDs at wavelengths of 630 nm (red), 515 nm (green), and 410-456 nm (blue) did not influence the reduction in cell viability.…”
Section: Biological Assaysupporting
confidence: 76%
“…Et when comparing the two types of treatments, PDT and dark. This low reduction in cell viability is not related to exposure to LED, considering that cell viability is higher when cells were exposed to PDT (Figure 5A), which was also observed in studies by Shah et al [31], in which they evaluated the photodynamic activity of four types of LEDs when cancer cells were exposed to them. Furthermore, it was observed that LEDs at wavelengths of 630 nm (red), 515 nm (green), and 410-456 nm (blue) did not influence the reduction in cell viability.…”
Section: Biological Assaysupporting
confidence: 76%
“…Thus, there is an unmet need for new therapeutic approaches to augment and improve the current standard of care for ES. Although 5-ALA-mediated PDT has been shown to be a viable therapeutic option for the treatment of various types of cancer [ 18 , 30 , 36 ], its use with soft tissue sarcomas such as ES is not well documented. The goal of this study was to investigate the therapeutic effects of 5-ALA PDT and DOX on ES cell lines, both individually and in combination.…”
Section: Discussionmentioning
confidence: 99%
“…As 5-ALA and thus PPIX are specifically enriched in brain tumors, their application in PDT was expected to be a promising approach. Several studies were performed to investigate the potential of 5-ALA-PDT for PDT applications (17)(18)(19). Eskiler et al demonstrated the effectiveness of 5-ALA-PDT in the treatment of breast cancer (20), whereas its photodamaging capabilities on rhabdomyosarcoma were shown by Atif et al (21).…”
Section: Introductionmentioning
confidence: 99%